Девочка с Земли: [для среднего школьного возраста] / Кир Булычев - Булычев Кир (Школьная библиотека, 2016)
Экземпляры: (20171031) / Инвентарный номер: 4730 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 90 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6